Pelatihan Keluarga Lansia ( BKL) Dalam Meningkatkan Kesehatan Gigi Lansia - Ainun Mardiah; Cut Aja Nuraskin (Poltekkes Kemenkes Aceh, 2022)
Elderly is a process of changing the function of body tissues and organs, there is a decrease in the ability of various body tissues. The decrease in this condition occurs in various organs of the body, including weakened memory, sensory changes, and changes in dental and oral health. Dental and oral problems can affect the nutritional status and health of the elderly. The number of malnourished elderly in Indonesia is 3.4% and 96% of the elderly experience dental caries. Seeing this phenomenon, the health of the elderly needs to be improved, especially dental and oral health so that there is a nutritional balance and affects the general condition of the elderly. This is the background for the service team to provide training on